Canine insulinomas appear hyperintense on MRI T2‐weighted images and isointense on T1‐weighted images. Issue 3 (17th January 2019) - Walczak, Raelyn; Paek, Matthew; Uzzle, Matthew; Taylor, Jim; Specchi, Swan
Abstract: Clinical and imaging diagnosis of canine insulinomas has proven difficult due to nonspecific clinical signs and the small size of these tumors. The aim of this retrospective case series study was to describe MRI findings in a group of dogs with pancreatic insulinomas. Included dogs were presented for suspected pancreatic insulinoma, MRI was used to assist with localization of the primary lesion, and the diagnosis was confirmed with surgical exploratory laparotomy and histopathology. The MRI studies for each dog were retrieved and the following data were recorded: T1‐weighted and T2‐weighted signal intensities, type of contrast enhancement, size and location of the primary lesion, and characteristics of metastatic lesions (if present). A total of four dogs were sampled. In all patients, the insulinoma displayed high‐intensity signal on T2‐weighted fat saturation images, similar to human studies. On postcontrast T1‐weighted fat saturation images, the tumors were primarily isointense to normal pancreatic tissue, in contrast to human studies where a low‐intensity signal is typically identified. Abnormal islet tissue was detected with MRI in all four dogs and metastases were identified in three dogs. Variations in the MRI appearance of primary and metastatic lesions were identified and could have been related to the variation of tissue composition, including the presence of neoplastic cells, hemorrhage, and fibrovascular stroma, and to the transformation of this tissue throughout the disease process.